Physical and virtual carbon metabolism of global cities - Shaoqing Chen (Nature Portfolio, 2020)
Activities in cities are important drivers of global carbon fluxes. Here the authors trace the carbon metabolism in 16 global cities in terms of both physical and virtual carbon inflows, stock changes and outflows in relation to the supply chains of urban production and consumption and show that the total carbon impacts of global cities are found to be highly varied in either per capita, intensity or density measures.